Use of 3D printing in preoperative planning and training for aortic endovascular repair and aortic valve disease - Gomes, Eduardo Nascimento (2018)
Introduction: Three-dimensional (3D) printing has become an affordable tool for assisting heart surgeons in the aorta endovascular field, both in surgical planning, education and training of residents and students. This technique permits the construction of physical prototypes from conventional medical images by converting the anatomical information into computer aided design (CAD) files. Objective: To present the 3D printing feature on developing prototypes leading to improved aortic endovascular surgical planning, as well as transcatheter aortic valve implantation, and mainly enabling training of the surgical procedure to be performed on patient's specific condition. Methods: Six 3D printed real scale prototypes were built representing different aortic diseases, taken from real patients, to simulate the correction of the disease with endoprosthesis deployment. Results: In the hybrid room, the 3D prototypes were examined under fluoroscopy, making it possible to obtain images that clearly delimited the walls of the aorta and its details. The endovascular simulation was then able to be performed, by correctly positioning the endoprosthesis, followed by its deployment. Conclusion: The 3D printing allowed the construction of aortic diseases realistic prototypes, offering a 3D view from the two-dimensional image of computed tomography (CT) angiography, allowing better surgical planning and surgeon training in the specific case beforehand.